Pengaruh Due Professional Care, Locus Of Control, dan Pengalaman Auditor Terhadap Kualitas Audit dengan Skeptisme Profesional Sebagai Variabel Moderasi Pada Auditor di Kantor Akuntan Publik Kota Medan - Diva Eldora Purba; Yulita Triadiarti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
With professional skepticism serving as a moderating variable among auditors employed by public accounting firms in Medan, this study seeks to examine the impact of due professional care, locus of control, and auditor experience on audit quality. The study employed a survey method with a quantitative approach, collecting data via questionnaires given to auditors. The SPSS software was then used to analyze the gathered data using multiple linear regression with moderation analysis. The findings demonstrated that audit quality was significantly impacted by locus of control, proper professional care, and auditor experience. Furthermore, it was discovered that professional skepticism moderated the association between locus of control and audit quality, but it had no moderating effect on the impact of auditor experience and due professional care on audit quality. Overall, these results support the idea that professional attitudes and internal auditor traits are crucial for raising audit quality